Exploring the intensive and extensive margins of world trade - Gabriel J. Felbermayr; Wilhelm K. Kohler (Center for Economic Studies and ifo Institute (CESifo), 2004)
World trade evolves at two margins. Where a bilateral trading relationship already exists it may increase through time (intensive margin). But trade may also increase if a trading bilateral relationship is newly established between countries that have not traded with each other in the past (extensive margin). We provide an empirical dissection of post-World-War- II growth in manufacturing world trade along these two margins. We propose a ?cornersolutions- version? of the gravity model to explain movements on both margins. A Tobit estimation of this model resolves the so-called ?distance-puzzle?. It also finds more convincing evidence than recent literature that WTO-membership enhances trade.
Keywords: F12; F15; 330; bilateral trade; globalization; gravity model; Außenwirtschaft; Internationale Wirtschaftsbeziehungen; Globalisierung; Gravitationsmodell; WTO-Beitritt; Schätzung; Welt